HUMOR IS NECESSARY FOR INTENSIFICATION LEARNING CREATIVE TECHNOLOGIES IN ENGINEERING EDUCATION - Valeriy Likholetov; Sergei Aliukov (International Journal of Engineering Education, 2021)
The article reveals the possibilities of using joke and cartoon as didactic tools that are adequate to the goals of "mass-education" of teaching creative technologies, where the theory of solving inventive problems (TRIZ) is a prominent representative today. These forms of humor have a range of unique properties and are therefore suitable for teaching different categories of students creative thinking procedures at all levels of training and self-education. An original method has been created, the essence of which is to gradually transform an joke and caricature in the classroom from passive (illustrative-relaxation) didactic tools into active ones, which increase the motivation and success of students ' activities by increasing their instrumental knowledge and skills to change systems of any nature (this is knowledge of the meta-level-knowledge-transformation and system knowledge). Algorithmic procedures for using these forms of humor have been tested in the University environment and the post-graduate education system (including teacher training), as well as in business education (in industrial companies, research centers and laboratories). The effectiveness and efficiency of using these non-standard didactic tools has been confirmed.